Squamous cell carcinoma complicating chronic osteomyelitis: A systematic review and case series. Issue 6 (December 2022) - Corrigan, Ruth Alexandra; Barlow, Glen; Hartley, Catherine; McNally, Martin
Abstract: Introduction: Squamous cell carcinoma (SCC) is a rare but serious complication of chronic osteomyelitis. This study aimed to determine an optimum approach to diagnosis and management. Methods: A systematic review was performed using Medline, Embase, CINAHL and Web of Science, from 1999-present. Additional cases, meeting the eligibility criteria, were added from our hospital database. Patient demographics (age, gender, co-morbidities), osteomyelitis diagnosis (location, duration), diagnosis of SCC (method, imaging, extent of disease) and management (amputation versus wide local excision versus palliation) as well as outcome at one and five years were collected. Results: Nineteen studies involving 106 patients met strict inclusion criteria. All published studies were case reports or case series. Chronic osteomyelitis had been present for a mean of 31 years (range 3–67) prior to SCC diagnosis. SCC was most commonly treated by amputation (81%). A poorer outcome occurred in those with metastatic disease (p = 0.006 at one year; p = 0.032 at five years), an incidental diagnosis at surgery for osteomyelitis (p = 0.052; p = 0.021) and SCC after pelvic osteomyelitis (p < 0.001; p = 0.002). Conclusions: SCC should be suspected in all cases of chronic osteomyelitis with skin changes, particularly if the duration of sinus drainage exceeds 3 years. Histological biopsy for malignancy should be taken in all suspected cases, as well as routinely during excision of osteomyelitis when chronic skin changes are present. Staging computed tomography (CT) scanning is recommended to guide adjunctive therapy. Amputation, where possible, may be considered as the definitive surgical management, after discussion with the patient. Highlights: Squamous carcinoma can develop within 3 years of osteomyelitis with sinuses. Biopsy and histology of sinus tissue may aid diagnosis. Early diagnosis may reduce poor outcomes from metastatic disease. Staging with CT scanning is appropriate to guide adjunctive therapy. Amputation may be the preferred treatment.